Ehrlichia canis rapid spread and possible enzooty in northern South Australia and distribution of its vector Rhipicephalus linnaei. Issue 11 (22nd August 2022) - Chaber, A‐L; Easther, R; Cumming, B; Irving, R; Keyburn, AL; Smart, C; O'Handley, R; Lignereux, L
Abstract : Recent concerns have arisen in Australia regarding detections of the exotic bacterium Ehrlichia canis which has resulted in ehrlichiosis outbreaks. In Australia, it is spread by the tropical brown dog tick Rhipicephalus linnaei, formerly Rhipicephalus sanguineus sensu lato tropical lineage. Previously, the tick has been recorded in South Australia in the Coober Pedy and the Oodnadatta areas. This study, which includes historical specimens data held in historical Australian arthropod collections, along with 10 sampled remote communities, confirms the wide distribution range of this species within the State. E. canis was detected by PCR in the ticks. The percentage of dogs hosting PCR‐positive ticks increased from 2.8% (95% confidence interval [CI]: 0.3 to 9.7) in November–December 2020 to 62.9% (95% CI: 44.9 to 78.5) end of February 2021, initially in two then in seven Anangu Pitjantjatjara Yankunytjatjara lands communities in the far northern regions of South Australia. Our results suggest a rapid spread of the pathogen. No evidence of E. canis was found in nine regional communities. The extended tropical brown dog tick distribution indicates a greater area where E. canis may occur and may require management to minimise the impacts of ehrlichiosis outbreaks. Without the implementation of effective detection and control programs, this extended distribution of R. linnaei is likely to result in the spread of the bacterium to other regions.